A mechanism for immediate reduction in mitral regurgitation after Cardiac resynchronization therapy: Insights from mechanical activation strain mapping - KANZAKI, Hideaki; BAZAZ, Raveen; SCHWARTZMAN, David; DOHI, Kaoru; SADE, L. Elif; GORCSAN, John III (Journal of the American College of Cardiology, 2004)
We tested the hypothesis that an immediate reduction in mitral regurgitation (MR) after cardiac resynchronization therapy (CRT) results from improved coordinated timing of the papillary muscle insertion sites, using the novel approach of mechanical activation strain mapping. Heart failure patients with left bundle branch block often benefit acutely from CRT; however, the role and mechanism of reduction of MR are unclear. Twenty-six consecutive patients undergoing CRT with at least mild MR were studied (ejection fraction 24 +/- 6%; QRS duration 168 +/- 30 ms). Echocardiographic Doppler and strain imaging was performed immediately before and the day after CRT, as well as in 10 normal control subjects. Mechanical activation sequence maps were constructed using longitudinal strain from 12 basal and mid-LV sites, with color coding of time-to-peak strain. Mitral regurgitation by the volumetric method consistently decreased after CRT: regurgitant volume from 40 +/- 20 ml to 24 +/- 17 ml and regurgitant fraction from 40 +/- 12% to 25 +/- 14% (both: p < 0.001 vs. baseline). Normal controls had uniform segmental time-to-peak strain, with a difference of only 12 +/- 8 ms between all segments. In contrast, CRT patients at baseline had a 106 +/- 74 ms time delay between papillary muscle insertion sites (p < 0.001 vs. normal). This interpapillary muscle time delay shortened after CRT to 39 +/- 43 ms (p < 0.001 vs. baseline) and was significantly correlated with reductions in mitral regurgitant fraction (r = 0.77, p < 0.001). Cardiac resynchronization therapy significantly and immediately reduced MR. Improved coordinated timing of mechanical activation of papillary muscle insertion sites appears to be a mechanistic contributor to immediate MR reduction by CRT.